1989
DOI: 10.1088/0029-5515/29/12/006
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of energetic neutral beams into fusion plasmas

Abstract: The efficiency of neutral beam heating and current drive depends crucially on the deposition of the energy and momentum of the beam in the plasma. This deposition is determined by the atomic processes involved in the stopping (or effective ionization) of the neutral beam atoms. These processes have been studied in detail for the energy range from 10 keV/u to 10 MeV/u. The processes considered include both the ground state and the excited state of the beam atoms, thus allowing for the multistep ionization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
3
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 26 publications
4
133
3
7
Order By: Relevance
“…Fluctuations in the observed signal are directly proportional to the local density fluctuations through a proportionality constant that depends on local electron temperature and density: dn/nϭK(T e ,n e )dI/I. 6,7 The neutral beam viewing optical system consists of a custom-designed f /2, f ϭ40 cm, objective lens, 25 cm vacuum window, in-vessel shutter, optical axis-folding mirrors ͑to avoid a toroidal field coil͒ and scannable 2D motorized fiber-mounting array, all shown in Fig. 1.…”
Section: Diii-d Bes Diagnostic Systemmentioning
confidence: 99%
“…Fluctuations in the observed signal are directly proportional to the local density fluctuations through a proportionality constant that depends on local electron temperature and density: dn/nϭK(T e ,n e )dI/I. 6,7 The neutral beam viewing optical system consists of a custom-designed f /2, f ϭ40 cm, objective lens, 25 cm vacuum window, in-vessel shutter, optical axis-folding mirrors ͑to avoid a toroidal field coil͒ and scannable 2D motorized fiber-mounting array, all shown in Fig. 1.…”
Section: Diii-d Bes Diagnostic Systemmentioning
confidence: 99%
“…The aim of this work is firstly to study the differences of charge exchange cross sections at low energies in [21] and secondly, to recommend accurate ionization cross sections for collisions with H(n = 1, 2), which are of interest for the beam penetration into the plasma [37,38]. The calculations have been carried out by employing a CTMC method with improved initial distributions.…”
Section: +mentioning
confidence: 99%
“…Its convolution with the fusion cross-sections from [19] and a maxwellian distribution yields the beam-plasma fusion rate, whereas a self-convolution returns the beam-beam reaction rate. For the beam ionisation the Janev model [20][21] is used. A dedicated study has shown that using different beam stopping cross sections has a negligible effect on the NBI deposition profile for ASDEX Upgrade H-mode discharges [21].…”
Section: Modelling Assumptionsmentioning
confidence: 99%